Rancang Bangun Aplikasi Edukasi Interaktif Pengenalan Pahlawan Indonesia Menggunakan Algoritma Fisher-Yates - Nadhif Nandana Kartomo; Salmon Salmon; Rizky Zakariyya Rasyad (Bulletin of Computer Science Research, 2025)
This research was conducted to develop an interactive media application for introducing the names of Indonesian national heroes. If successful, this research is expected to provide users with an easier way to learn and recognize Indonesian national heroes. The study was carried out at SMP 21 Samarinda. The data collection methods used were observation, in which direct observations were conducted at SMP 21 Samarinda, and interviews, involving direct question-and-answer sessions related to the objectives of the research. The system development tools used in this study were Adobe Flash CS6 and Adobe Photoshop CS6. The final result of this research is an interactive media application for introducing the names of Indonesian national heroes, implementing the Fisher-Yates shuffle algorithm to make the learning experience more engaging and easier to understand for users.